Neurocutaneous Syndromes and Epilepsy - MİDİ, İPEK (KARE PUBL, 2016)
Objectives: Neurocutaneous syndromes are genetic diseases that affect the nervous system and the skin. Epileptic seizures are seen with variable frequency. In the present study, data of 29 patients from 5 centers were analyzed in an effort to draw attention to the disease group. Methods: Data of 29 patients diagnosed with neurocutaneous syndrome were retrospectively evaluated. Results: Study population was composed of 15 women (51.7%) and 14 men (48.3%), with a mean age of 31 (72 +/- 2.16). Ten patients (34.5%) were diagnosed with tuberous sclerosis, 9 (31%) with Sturge-Weber syndrome, 3 (10.3%) with neurofibromatosis type 1, 3 (10.3%) with neurofibromatosis type 2, 1 (3.4%) with neurocutaneous melanosis, 1 (3.4%) with hypomelanosis of Ito, 1 (3.4%) with probable Sturge-Weber syndrome, and 1 patient was diagnosed with unclassified neurocutaneous syndrome. One patient did not receive antiepileptic treatment, 9 (31%) received monotherapy, and 19 (65.5%) received polytherapy. Carbamazepine was the most commonly used medication. Conclusion: Attention is drawn to the prevalence of neurocutaneous syndrome in epileptic adults, with seizure frequency depending on syndrome type.
Keywords: Epilepsy; seizure; neurocutaneous syndromes; TUBEROUS SCLEROSIS COMPLEX; STURGE-WEBER SYNDROME